1985
DOI: 10.1523/jneurosci.05-05-01346.1985
|View full text |Cite
|
Sign up to set email alerts
|

A description of the GABAergic neurons and axon terminals in the motor nuclei of the cat thalamus

Abstract: The GABA neurons and their processes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
18
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 1 publication
3
18
0
Order By: Relevance
“…Moreover, long-latency disinhibition or delayed IPSPs observed after stimulation of substantia nigra (SNr) or deep cerebellar nuclei, respectively, are usually ascribed to effects mediated by LCN. Just as it has been previously demon strated in the cat [10], the present study confirmed that in the primate motor thalamus the LCN are GAD positive; therefore, the inhibitory nature of these interneurons and of the synapses formed by their den drites leaves little doubt. Similarly, cortical inputs to PN, when medi ated by LCN dendrites, are expected to be inhibitory, which is consis tent with demonstration of EPSP/IPSP sequences in the thalamus after cortical stimulation [for a review see ref .…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, long-latency disinhibition or delayed IPSPs observed after stimulation of substantia nigra (SNr) or deep cerebellar nuclei, respectively, are usually ascribed to effects mediated by LCN. Just as it has been previously demon strated in the cat [10], the present study confirmed that in the primate motor thalamus the LCN are GAD positive; therefore, the inhibitory nature of these interneurons and of the synapses formed by their den drites leaves little doubt. Similarly, cortical inputs to PN, when medi ated by LCN dendrites, are expected to be inhibitory, which is consis tent with demonstration of EPSP/IPSP sequences in the thalamus after cortical stimulation [for a review see ref .…”
Section: Discussionsupporting
confidence: 89%
“…Similar attempts to assess terminal distribution have been performed on four TCNs (Wilson et al, 1984), two TCNs (Raczkowski et al, 1988), and one LCN (Hamos et al, 1985) in the cat LGN. Although previous studies implied that afferents to TCNs are spatially segregated in the VL, this implication was derived from observations of short and limited segments of dendrites (Rinvik and Grofová, 1974a;Kultas-Ilinsky et al, 1985;Kultas-Ilinsky and Ilinsky, 1991;Sawyer et al, 1994;Mason et al, 1996;Sato et al, 1996). Precise quantitative information about the distribution of different types of synapses on single identified VL neurons was previously lacking.…”
Section: Discussionmentioning
confidence: 99%
“…8A-D). Because thalamic LCNs are GABAergic (Sterling and Davis, 1980;Ohara et al, 1983;Kultas-Ilinsky et al, 1985;Ohara et al, 1989), excitation of cerebellar terminals can release GABA from PSDs to TCNs, and thereby inhibit the TCNs. This agrees with the electrophysiological result that cerebellar stimulation evokes disynaptic inhibition in TCNs (Uno et al, 1970;Shinoda et al, 1985a;Rispal-Padel et al, 1987;Ando et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flattened vesicle-filled profiles of this type also exist in other thalamic nuclei and have been referred to as either an F2 bouton (Guillery, 1969), presynaptic dendrite (PSD; Ralston, 19711, ID bouton (Famiglietti and Peters, 19721, or P bouton (Lieberman and Webster, 1974;Ohara et al, 1983). They have been shown to be dendritic processes of LCNs (Famiglietti and Peters, 1972) which histochemically show y-aminobutyric acid (GABA, Sterling and Davis, 1980;Ohara et al, 1989) and glutamic acid decarboxylase (GAD; Hendrickson et al, 1983;Kultas-Ilinsky et al, 1985). However, the boutons of this type were not identified in the rat, since LCNs do not exist in the rodent VL (Sawyer et al, 1994).…”
mentioning
confidence: 99%